Annabelle comes home - Dauberman, Gary; Safran, Peter 1965-; Wan, James 1977-; Wilson, Patrick 1973-; Farmiga, Vera; Grace, Mckenna 2006-; Iseman, Madison 1997-; Sarife, Katie 1993-; Bishara, Joseph; Morri, Kirk; Burgess, Michael (Cinematographer); New Line Cinema Corporation; et al. (Burbank, CA Warner Bros. Home Entertainment, 2019)
Determined to keep Annabelle from wreaking more havoc, demonologists Ed and Lorraine Warren bring the possessed doll to the locked artifacts room in their home, placing her 'safely' behind sacred glass and enlisting a priest's holy blessing. But an unholy night of horror awaits as Annabelle awakens the evil spirits in the room, who all set their sights on a new target, the Warrens' ten-year-old daughter, Judy, and her friends.
Originally released as a motion picture in 2019.
Sequel to the 2017 film : Annabell: Creation.
Wide screen.
Special feature: Behind the scenes : the werewolf.
Music, Joseph Bishara ; editor, Kirk Morri ; director of photography, Michael Burgess.
Mckenna Grace, Madison Iseman, Katie Sarife; Patrick Wilson, Vera Farmiga.
Keywords: Dolls -- Drama; Demonology -- Drama; Detective and mystery films; Drama; Feature films; Fiction films; Horror films; Thrillers (Motion pictures); Video recordings for people with visual disabilities; Video recordings for the hearing impaired